2014
DOI: 10.1080/00380768.2014.919834
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the water balance of irrigated paddy fields in SWAT 2009 using the curve number procedure and the pothole module

Abstract: The Soil and Water Assessment Tool (SWAT), a basin-scale hydrological and water quality simulation model, has become popular in Asia for assessing the impacts of land use and human activities including paddy rice (Oryza sativa L.) cultivation which is a typical agricultural management system in Asia. The water ponding and drainage management in paddy fields should significantly affect the regional hydrology and water quality; however, the suitability of SWAT for simulating paddy hydrology at a field scale has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…A decrease in ET is normally caused by a decrease in P and/or PET (Sun et al, 2005;Sun et al, 2011aSun et al, , 2011b. Our data suggested that the decrease in ET was not caused by PET or P because annual and growing-season PET significantly increased and overall precipitation did not change significantly.…”
Section: Increased Stream Flow Explained By the Decreases In Et And Laimentioning
confidence: 54%
See 2 more Smart Citations
“…A decrease in ET is normally caused by a decrease in P and/or PET (Sun et al, 2005;Sun et al, 2011aSun et al, , 2011b. Our data suggested that the decrease in ET was not caused by PET or P because annual and growing-season PET significantly increased and overall precipitation did not change significantly.…”
Section: Increased Stream Flow Explained By the Decreases In Et And Laimentioning
confidence: 54%
“…Second, regional annual ET is generally controlled by PET, P , and land surface conditions (Sun et al, 2005). A decrease in ET is normally caused by a decrease in P and/or PET (Sun et al, 2005;Sun et al, 2011aSun et al, , 2011b.…”
Section: Increased Stream Flow Explained By the Decreases In Et And Laimentioning
confidence: 99%
See 1 more Smart Citation
“…However, improvement of the SWAT modelling in tropical regions is needed as it was initially constructed based on the climate and environmental conditions in the United States. For example, in recent years, some studies have been conducted to improve the paddy module within the SWAT model [39,40]. As oil palm plantation is a major crop in tropical countries including Malaysia, Indonesia, and some African countries, so modification of the oil palm module might be able to increase the reliability of the SWAT model in the tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Computation techniques for Qsurf and IR are described in the following sections. In SWAT-PADDY, the method to compute percolation of water from impoundment to soil which is used in the original or modified pothole [28,31] was not adopted, because soil water content and saturated hydraulic conductivity of surface soil layers are only the elements to determine the percolation rate and this leads to much underestimation of percolation in paddy fields [27]. In actual paddy fields, there is a constant water loss as a seepage through bund of paddy field and vertical percolation even though surface soils are saturated and hydraulic conductivity is very low because of puddling operation.…”
Section: Development Of Paddy Impoundment Modulementioning
confidence: 99%